Determination of antioxidant in 3 in 1 instant coffees in malaysia market by using ferric reducing antioxidant power (frap) assay / Farah Amirah Azmi - Azmi, Farah Amirah (Faculty Of Applied Sciences, 2017)
Coffee beverage is one of the most beverages that are consumed by the people around the world. It is rich with the antioxidant compounds which will help to protect human body against from the effect of dangerous free radicals. In this study, seven different brands of 3 in 1 instant coffee were purchased from the local market to determine the antioxidant content. Ferric Reducing Antioxidant Power (FRAP) assay was used to determine the antioxidant capacity in coffee samples and analyzed by using UV-Vis spectrophotometer at 536 nm. The samples were extracted by using water as a solvent which followed the daily dietary method used by the consumer. Brand that exhibit the highest antioxidant content was brand SS with the FRAP value 285.94 µ.M Fe [II]/mL coffee. Brand IC had the lowest antioxidant content with the FRAP value 182.87 µ.M Fe (II)/mL coffee. Therefore, consumers have reliable information to choose the best brand of 3 in 1 instant coffee for the daily intake.